2014
DOI: 10.1093/ijnp/pyu001
|View full text |Cite|
|
Sign up to set email alerts
|

Carrier-Mediated Cocaine Transport at the Blood-Brain Barrier as a Putative Mechanism in Addiction Liability

Abstract: Background:The rate of entry of cocaine into the brain is a critical factor that influences neuronal plasticity and the development of cocaine addiction. Until now, passive diffusion has been considered the unique mechanism known by which cocaine crosses the blood-brain barrier.Methods:We reassessed mechanisms of transport of cocaine at the blood-brain barrier using a human cerebral capillary endothelial cell line (hCMEC/D3) and in situ mouse carotid perfusion.Results:Both in vivo and in vitro cocaine transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 40 publications
2
52
0
Order By: Relevance
“…[ 3 H]‐clonidine (2.27 MBq·mmol −1 ), [ 3 H]‐naloxone (2.06 MBq·mmol −1 ) and [ 3 H]‐(−)cocaine (1.31 MBq·mmol −1 ) were purchased from Perkin Elmer (Courtaboeuf, France). Drugs were obtained as reported (Chapy et al , ). Compounds 1 to 10 were purchased from Specs (Delft, the Netherlands), and other chemicals were from Sigma (Saint Quentin‐Fallavier, France).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 3 H]‐clonidine (2.27 MBq·mmol −1 ), [ 3 H]‐naloxone (2.06 MBq·mmol −1 ) and [ 3 H]‐(−)cocaine (1.31 MBq·mmol −1 ) were purchased from Perkin Elmer (Courtaboeuf, France). Drugs were obtained as reported (Chapy et al , ). Compounds 1 to 10 were purchased from Specs (Delft, the Netherlands), and other chemicals were from Sigma (Saint Quentin‐Fallavier, France).…”
Section: Methodsmentioning
confidence: 99%
“…Brain microdialysis studies suggested that this DPH influx is present in rat, dog and non‐human primate BBB (Sadiq et al , ; Shaffer et al , ). In vitro studies of rodent and human immortalized brain endothelium and intestinal cell lines established the presence of a cationic drug/proton antiporter with unique properties that did not correspond to any known SLC transporters: OCT1‐3 (SLC22A1‐3), OCTN (SLC22A4‐5) and MATE1 (SLC47A1) (Fischer et al , ; Kuwayama et al , ; Okura et al , ; Chapy et al , ). In vivo/in situ studies definitively confirmed that a functional novel drug/proton antiporter, molecularly unknown, is physiologically active at the mouse BBB and blood–retina barrier (André et al , ; Chapy et al , ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The rate at which drugs reach the brain parenchyma depends not only on their route of administration but also on their ability to cross the cerebral endothelium, also called the blood–brain barrier (BBB), which constitutes the main brain interface modulating the exchange of compounds between the brain and blood [50]. Alterations in BBB function are likely involved in drug abuse neurotoxicity [1, 86].…”
Section: Transendothelial Blood–brain Barrier Dysfunctionmentioning
confidence: 99%